High Precision Fertilizer Applicator For Industrial Plantation: Discrete Element Method Simulation And Prototyping - Nurprasetio, Ignatius Pulung; Febriansyah, Adit; Widyantara, Robby Dwianto; Budiman, Bentang Arief (Jurnal Keteknikan Pertanian, 2022)
We designed a high-precision fertilizer applicator to distribute fertilizer with the required dose at every specified point. The dose necessary aims to meet the nutritional needs of plants, so that plant growth is more effective while reduce waste. The fertilizer applicator was designed to have an auger and drive system that can discharge the fertilizer precisely. A 3D CAD model of the applicator was created to conduct a discrete element simulation to predict the discharge fertilizer process. Experiment was carried out to validate the simulation model. The experiment utilized a small-scale applicator prototype manufactured by 3D printing. A small electric actuator controlled by Arduino microcontroller was installed to rotate the auger. The auger can push and release the fertilizer precisely depending on the rotation’s number. Both simulation and experiment results were compared and showed a small error of 6.42%. The results show our designed fertilizer applicator have good accuracy and precision, which indicates the applicator was suitable to distribute fertilizer uniformly.